2018
DOI: 10.1534/genetics.118.301349
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Promotes the Interaction of the FAcilitates Chromatin Transactions (FACT) Complex with Nucleosomes inSaccharomyces cerevisiae

Abstract: The FACT (FAcilitates Chromatin Transactions) complex is a conserved complex that maintains chromatin structure on transcriptionally active genes. Consistent with this, FACT is enriched on highly expressed genes, but how it is targeted to these regions is unknown. In vitro, FACT binds destabilized nucleosomes, supporting the hypothesis that FACT is targeted to transcribed chromatin through recognition of RNA polymerase (RNAP)-disrupted nucleosomes. In this study, we used high-resolution analysis of FACT occupa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
40
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(57 citation statements)
references
References 102 publications
12
40
0
Order By: Relevance
“…Our current model of FACT function is consistent with published structural studies that showed that mammalian FACT could only bind nucleosomal components or partially disassembled nucleosomes (e.g., lacking the H2A/H2B dimer) because the FACT binding epitopes are hidden within the folded nucleosome (Tsunaka et al 2016;Safina et al 2017;Wang et al 2018). It is also consistent with studies in yeast that showed that FACT is targeted to transcribed chromatin through its recognition of RNA polymerase-disrupted nucleosomes (Martin et al 2018) If the above model is correct, why is transcription increased following the loss of FACT? There are two potential explanations for this phenomenon, which will require further investigation.…”
Section: Discussionsupporting
confidence: 90%
“…Our current model of FACT function is consistent with published structural studies that showed that mammalian FACT could only bind nucleosomal components or partially disassembled nucleosomes (e.g., lacking the H2A/H2B dimer) because the FACT binding epitopes are hidden within the folded nucleosome (Tsunaka et al 2016;Safina et al 2017;Wang et al 2018). It is also consistent with studies in yeast that showed that FACT is targeted to transcribed chromatin through its recognition of RNA polymerase-disrupted nucleosomes (Martin et al 2018) If the above model is correct, why is transcription increased following the loss of FACT? There are two potential explanations for this phenomenon, which will require further investigation.…”
Section: Discussionsupporting
confidence: 90%
“…Initial models suggested that FACT's ability to destabilize nucleosomes is required to support transcription elongation. However, FACT mutations do not appear to affect the rate of elongation in vivo (Mason and Struhl 2005;Biswas et al 2006;Kuryan et al 2012), and recent results show that FACT localizes to transcription units primarily as a response to exposure of its binding sites by ongoing transcription (Martin et al 2018). In this emerging view, FACT has a more prominent role in recovering from chromatin disruptions caused by transcription than in supporting the progression of transcription.…”
Section: Discussionmentioning
confidence: 99%
“…However, attempts to detect the predicted decrease in the rate of RNA Pol II elongation in FACT mutants have had mixed results, with some reporting indirect effects (Fleming et al 2008) but others finding no changes (Mason and Struhl 2005;Biswas et al 2006;Kuryan et al 2012). Recent work indicates that FACT occupancy is driven by exposure of its binding sites as nucleosomes are disrupted by transcription, suggesting that FACT responds to transcription rather than facilitating it (Martin et al 2018). If FACT or H3-K56ac promote polymerase progression, mutations could affect initiation (the ability to convert an initiation complex to an elongation complex by overcoming the initial barrier posed by the +1 nucleosome) or elongation (the ability to progress efficiently through each successive nucleosome encountered throughout transcription units).…”
Section: Fact and H3 Mutations Caused Similar Defects In Transcript Amentioning
confidence: 99%
See 1 more Smart Citation
“…Although no current crystal structures of Spt16 and histones show an interaction between Spt16 and the nucleosome acidic patch, it is likely that FACT recognition of the nucleosome is highly dynamic in vivo and interactions between Spt16 and the acidic patch may primarily occur in the context of active transcription. Indeed, a recent study found that transcription-disrupted nucleosomes enhance FACT binding to chromatin (89).…”
Section: Discussionmentioning
confidence: 99%